Schwann Cells Contribute to Alveolar Bone Regeneration by Promoting Cell Proliferation. (13th November 2022) - Zhang, Xiaohan; Xiong, Qiuchan; Lin, Weimin; Wang, Qian; Zhang, Danting; Xu, Ruoshi; Zhou, Xinyi; Zhang, Shiwen; Peng, Lin; Yuan, Quan
ABSTRACT: The plasticity of Schwann cells (SCs) following nerve injury is a critical feature in the regeneration of peripheral nerves as well as surrounding tissues. Here, we show a pivotal role of Schwann cell‐derived cells in alveolar bone regeneration through the specific ablation of proteolipid protein 1 (Plp)‐expressing cells and the transplantation of teased nerve fibers and associated cells. With inducible Plp specific genetic tracing, we observe that Plp + cells migrate into wounded alveolar defect and dedifferentiate into repair SCs. Notably, these cells barely transdifferentiate into osteogenic cell lineage in both SCs tracing model and transplant model, but secret factors to enhance the proliferation of alveolar skeletal stem cells (aSSCs). As to the mechanism, this effect is associated with the upregulation of extracellular matrix (ECM) receptors and receptor tyrosine kinases (RTKs) signaling and the downstream extracellular signal‐regulated kinase (ERK)/mitogen‐activated protein kinase (MAPK) pathway and the phosphoinositide 3‐kinase–protein kinase B (PI3K‐Akt) pathway. Collectively, our data demonstrate that SCs dedifferentiate after neighboring alveolar bone injury and contribute to bone regeneration mainly by a paracrine function. © 2022 American Society for Bone and Mineral Research (ASBMR).